Respuesta :

Answer:

[tex]-9x^2[/tex]

Step-by-step explanation:

Composition of two functions can be obtained by replacing inner function in place of x of outer function and then plugging back the actual value of inner function  f(x) and then simplifying it gives g(f(x)) which is usually called gof(x) .

f(x) = -[tex]-3x^2[/tex]

g(x) = 3x

g(f(x) ) = 3 f(x)

            =3 ([tex]-3x^2[/tex])

            = [tex]-9x^2[/tex]

Answer:

-9x²

Step-by-step explanation:

We have given two functions.

We have to find their composition.

f(x) = -3x²   and g(x) = 3x

(gof)(x) = g(f(x)) = ?

Firstly , we have to put the value of f(x) in g(f(x)).

Putting given values, we have

g(f(x)) = g(-3x²)

g(f(x)) = 3(-3x²)

g(f(x)) = -9x² which is the answer.

Otras preguntas